A resistência e a sobrevivência das professoras na rede pública estadual de Santa Maria - Alves, Maria Tereza Silva (2022)
This study, developed in Research Line 2 – Teacher Training Professional and Technological Education, sought a discussion about the triple working hours of teachers. The Project emerged from the observations of the researcher, who is a state teacher, from the perspective of gender studies, and investigated the participation of women, teachers, in state schools covering Santa Maria, as well as the female presence, their historicity, with emphasis on to the heart of RS, reflecting the illusory fragility of being a woman to the undeniable resistance of continuing to fight, the patriarchal system and the illness of teachers and their absences on LTS (health leave), in the period from 2018 to 2021. In this study, we opted for documental research, having as support the bibliographic survey, through consultation of books and scientific articles and the decolonial methodological theoretical approach in the Freirian perspective. Based on documents provided by the State Department of Education, it was proposed to analyze the number of absences in LTS, of teachers from the State Public Network, covering Santa Maria. The study was structured in four chapters. In the first one, the historicity of the EPT in Brazil and in the city of Santa Maria, the Pandemic Scenario and the Triple Journey of Teachers were built, seeking to expose the theoretical framework that supported the study. In the second chapter, it brought the researcher's life story and an approach about Feminism, Decolonity and Epistemologies in the So-called Global South. The Third Chapter addressed the Patriarchy of gender relations and its influences, the feminization of teaching, giving relevance to teaching work, and to female teaching as resistance. Subsequently, the fourth chapter dealt with the effects of work overload on the health of teachers, and the illness of teachers, possible causes and absences – LTS (health leave) from the classroom. As a questioning, it was intended to investigate whether the overload of the triple shift is a determining factor for the illness and, for this, we used the analysis of documents provided by SEDUC where it was possible to observe the number of medical reports of the professors for absence from the service. However, in the pandemic, it was observed that the illness stopped due to remote and hybrid teaching to better understand the impact of the pandemic period on Education. The choice and delimitation of the theme aimed to satisfy the requirements of the line of research in which it is inserted, referring to “Teacher Training for Vocational and Technological Education” (LP 2).